Pura Mangkunegaran dan Keraton Kasunanan Surakarta sebagai Sarana Wisata Edukasi Sejarah - Puspitasari, Anugrahaning Della; Natalia, Devina Christy; Marsudi, Mahawi; Marmoah, Sri (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Mangkunegaran Temple and Surakarta Kasunanan Palace as Historical Education Tourism Facilities This article discusses Pura Mangkunegaran and Keraton Kasunanan Surakarta as historical education tourism destinations in Surakarta City. In this activity, a qualitative descriptive approach was used, with data collected through observation, interviews, documentation, and literature study. The keraton, which serves as the residence of the king and the center of government, holds significant historical value. The results show that both keraton have museums that are highly potential as historical education tourism attractions. Additionally, each keraton has its own unique characteristics that can serve as an attraction for visitors. Overall, the activity concludes that historical education tourism aims to enrich visitors' knowledge and understanding of history. Surakarta City, with Pura Mangkunegaran and Keraton Kasunanan, offers two complementary historical education tourism destinations, with similarities and differences related to their origins, royal titles, and the historical collections housed in the museums..